Radiotherapy in the adjuvant setting of cervical carcinoma: treatment, results, and prognostic factors. Issue 4 (1st July 2007) - Atahan, I. L.; Yildiz, F.; Ozyar, E.; Pehlivan, B.; Genc, M.; Kose, M. F.; Tulunay, G.; Ayhan, A.; Yuce, K.; Guler, N.; Kucukali, T.
Abstract : To evaluate the efficacy of postoperative radiotherapy and to investigate prognostic factors for early-stage cervical cancer patients. From December 1993 to December 2001, 141 patients with stage I–II cervical cancer without para-aortic lymph node (LN) metastases and treated by surgery and postoperative radiotherapy (RT) were included in this study. Indications for postoperative external RT were based on pathologic findings, including LN metastasis, positive surgical margins, parametrial involvement, pT2 tumor, and presence of any two minor risk factors like lymphvascular space involvement, deep stromal invasion, and tumor diameter between 2–4 cm. Sixty-six (47%) patients received RT alone, whereas 59 (42%) were treated with RT and concomitant chemotherapy (CT), and 16 received neoadjuvant CT. Patients with positive vaginal margins also received 27.5 Gy high–dose rate vaginal cuff brachytherapy in five fractions. Median follow-up time was 55 months. The actuarial 5-year overall (OS), disease-free (DFS), locoregional recurrence-free (LRFS), and distant metastases-free (DMFS) survival rates are 70%, 68%, 77%, and 88%, respectively. Univariate and multivariate analyses revealed that level and number of metastatic LNs and concomitant CT were unique significant prognostic factors for OS, DFS, and LRFS. Endometrial involvement, on the other hand, was proven to be significant for DFS and DMFS. Patients with less than three LN metastases or having only obturator LN involvement showed similar prognosis with their counterparts having no LN metastases. On the other hand, patients with either common iliac LN or more than three LN metastases had significantly worse outcome. Our results indicate that level and number of metastatic LNs are the most important prognostic factors determining the survival rates, and patients with upper lymphatic involvement or more than three metastatic LNs seem to need more effective treatment approaches